Anti-Müllerian hormone (AMH) as a good predictor of time of menopause - Kruszyńska, Aleksandra; Słowińska-Srzednicka, Jadwiga (Menopause Review/Przegląd Menopauzalny, 2017)
Anti-Müllerian hormone (AMH) in women is secreted by granulosa cells in late preantral and small antral follicles. AMH seems to be a very stable marker having some advantages over other biochemical and biophysical markers and is very useful in the assessment of ovarian reserve. AMH measurement may be used in cases of premature ovarian failure, including iatrogenic, due to treatment for cancer, hypogonadotropic hypogonadism, and lastly, in polycystic ovary syndrome (PCOS). It is also a very specific marker of ovarian tumors – folliculomas. According to outcomes of some studies, AMH seems to be highly predictive for the timing of menopause. There are mathematical models in which a single AMH measurement is used to predict the time of menopause even in very young women, many years before the last period.